2023
DOI: 10.3389/fcell.2023.1207748
|View full text |Cite
|
Sign up to set email alerts
|

ROS-responsive exogenous functional mitochondria can rescue neural cells post-ischemic stroke

Abstract: Background: The transfer of mitochondria from healthy mesenchymal stem cells (MSCs) to injured MSCs has been shown to have potential therapeutic benefits for neural cell post-ischemic stroke. Specifically, functional mitochondria can perform their normal functions after being internalized by stressed cells, leading to host cell survival. However, while this approach shows promise, there is still a lack of understanding regarding which neural cells can internalize functional mitochondria and the regulatory mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…Some studies have found that administering exogenous mitochondria to the ischemic area can alleviate mitochondrial dysfunction. Exogenous mitochondria can use endogenous mechanisms to repair cellular damage, potentially resulting in therapeutic effects on the nerves after an IS [55][56][57].…”
Section: The Pathophysiology Of Issmentioning
confidence: 99%
“…Some studies have found that administering exogenous mitochondria to the ischemic area can alleviate mitochondrial dysfunction. Exogenous mitochondria can use endogenous mechanisms to repair cellular damage, potentially resulting in therapeutic effects on the nerves after an IS [55][56][57].…”
Section: The Pathophysiology Of Issmentioning
confidence: 99%